Effects of Freezing and Drying Methods on the Characteristics of Instant Corn Grits - Hernawaty Husain; Tien R Muchtadi; Sugiyono .; Bambang Haryanto (Jurnal Teknologi dan Industri Pangan, 2006)
Bassang is a traditional food of Makassar mainly made of corn grits. The food takes about 23 hours of traditional preparation. This lengthy process leads to a need for a technological innovation for a quicker preparation. In this study corn kernels were ground into grits. The corn grits were then gelatinized, frozen and dried using cabinet, fluidized bed, oven, and vacuum dryers. Soaking of kernels in 1% sodium citric followed by slow freezing yielded better results compared to soaking in calcium chloride followed by steaming and quick freezing. Oven drying yielded better results compared to cabinet, vacuum and fluidized bed drying, in relation to the porous characteristics and rehidration time. Instant corn grits can be cooked for 7 minutes. Key words : corn, bassang, drying, instant.